Enhancement of light collection through flexible polymeric films patterned using self-assembled photonic crystals. (2nd June 2015) - Haldar, Arpita; Reddy, M Srinivas; Vijaya, R
Abstract: Flexible nanopatterned polymeric thin films are fabricated by a simple and cost-effective soft imprint lithography technique. The use of low-cost self-assembled photonic crystals as structured masters is the highlight of this work. Two types of polymeric films, with and without a dye, are patterned. Both have shown very good anti-reflection properties and the dyed films have also shown a polarization-independent enhancement in the absorption for the normal incidence of light. The structures with smaller features have shown better anti-reflection properties. Angle-dependent reflection measurements show an improved reduction in reflection at larger incidence angles. A maximum reduction in reflection of 11% is obtained from the patterned film in comparison to the bare glass substrate when the light is incident at an angle of 60°. This is very useful in photovoltaic devices as wide-angle anti-reflection coating. The reflection calculated using the effective medium approximation supports the experimental results.